2004
DOI: 10.1039/b402649g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of benzo-fused lactams and lactones via Ru(ii)-catalyzed cycloaddition of amide- and ester-tethered α,ω-diynes with terminal alkynes: electronic directing effect of internal conjugated carbonyl group

Abstract: In the presence of a catalytic amount of Cp*RuCl(cod), 1,6- and 1,7-diynes connected by an amide or an ester tether underwent cycloaddition with terminal alkynes at room temperature to give rise to cycloadducts in 40-93% yields with 63 : 37-83 : 17 regioisomer ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 23 publications
4
24
1
1
Order By: Relevance
“…We previously found that such an unsymmetrical diyne reacted with terminal alkynes, electron-deficient nitriles, and isocyanates to give the corresponding cycloadducts with moderate to high regioselectivity. [5,10] In striking contrast, no regioselectivity was observed for the cycloadditions of 2h with malononitrile (3a) or chloroacetonitrile (3e), indicative of the cycloaddition with these nitriles proceeding via a different mechanism from the other examples. Moreover, we found that the similar cycloaddition of dichloroacetonitrile (3j) exhibited considerable regioselectivity, and the corresponding products 6hj and 7hj were obtained in a ratio of 80 : 20.…”
mentioning
confidence: 72%
“…We previously found that such an unsymmetrical diyne reacted with terminal alkynes, electron-deficient nitriles, and isocyanates to give the corresponding cycloadducts with moderate to high regioselectivity. [5,10] In striking contrast, no regioselectivity was observed for the cycloadditions of 2h with malononitrile (3a) or chloroacetonitrile (3e), indicative of the cycloaddition with these nitriles proceeding via a different mechanism from the other examples. Moreover, we found that the similar cycloaddition of dichloroacetonitrile (3j) exhibited considerable regioselectivity, and the corresponding products 6hj and 7hj were obtained in a ratio of 80 : 20.…”
mentioning
confidence: 72%
“…The [2 + 2 + 2] cyclotrimerization of alkynes to benzene derivatives is well-documented and reviewed earlier. [57] …”
Section: Synthesis Of Substituted Pyrone Pyran and Cyclohexadiene Dmentioning
confidence: 97%
“…They have started from anhydrides, [14] phthalimides, [15] β-hydroxy or β-phenylsulfanyl lactams [16,17] or 2-formylbenzoic acids. [18] Alternative methods such as condensations of imines with acetylene [19] or with an ester function [20] and treatment of an enamine with an aryl iodide [21] have also been reported. Whereas most of the previous strategies led easily to bis-aromatic fused heterocycles, synthetic pathways to design compounds of type V immediately appeared to be critical.…”
Section: Introductionmentioning
confidence: 98%